Heirs of oppression - Corlett, J. Angelo, 1958- (Studies in social, political, and legal philosophy., 2010)
Packing his case with moral argument and relevant facts, Angelo Corlett offers the most comprehensive defense to date in favor of reparations for African Americans and American Indians. As Corlett see it, the heirs of oppression are both the descendants of the oppressors and the descendants of their victims. Corlett delves deeply into the philosophically related issues of collective responsibility, forgiveness and apology, and reparations as a human right in ways that no other book or article to date has done.